Systematic Position of the Genus Nikanoria (Hymenoptera, Eurytomidae), with Description of Two New Species - Zerova, M.D.; Seryogina, L.Ya. (Вестник зоологии, 2012)
The genus name Nikanoria is resurrected from synonymy and considered to be separate from Bruchophagus based on analysis of morphological characters and trophic associations. Nikanoria pygmaea Zerova, sp. n. and N. deserta Zerova, sp. n. are described. На основании анализа морфологических и экологических особенностей видов рода Nikanoria отстаивается мнение о самостоятельности этого рода. Приводится описание двух новых видов — N. pygmaea Zerova, sp. n. и N. deserta Zerova, sp. n.